The The Function of Rechtsverwerking Regulation as an Instrument of Acquisition of Land Rights - Zahra, Farah Az; Syadza, Razanah; Natanegara, Mochammad Jermaen; Wiratmoko, Sharen Christina; Adliman, Fadilah (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
The function of rechtsverwerking regulation that contained in PP Number 24 of 1997 gives legal certainty to the acquisition of land rights. The abandonment of land carried out by a person of the community does not fulfill the obligation to maintain the land rights, which results in that person can lose the land rights and ends with the issuance of a new land certificate to a person or legal material that in good faith maintains the abandoned land. Rechtsverwerking is related to the social function of land that prioritizes the usefulness of the land among the community. The rechtsverwerking arrangement gives a five-year deadline to the party who feels they own the wasteland to sue the holder of a new certificate of the land. Some examples of rechtsverwerking is contained in Supreme Court Ruling No. 979/K/Sip/1971 and Supreme Court Review Decision Number 336 PK/Pdt/2015. The enforcement of the rechtsverwerking institution in Indonesia has not actually been able to be carried out according to its purpose, this is proven by the number of lawsuits against certificates in state courts or the cancellation of certificates in the State Administrative Court after five years since the issuance of new certificates. However, it does not mean that the certificate of land rights does not guarantee legal certainty, because the certificate is recognized as a strong evidence of rights.